The Indian summer monsoon and the South American summer monsoon and their responses to different forcings in some key periods of the Neogene - Carrasqueira, Igor Gustavo da Fonseca (2023)
In this work we present data from magnetic experiments and X-ray fluorescence for the record IODP U1471 located in the Maldives Inner Sea. Furthermore, we present data from magnetic experiments for the record NAP63 located in the São Paulo Bight. Magnetic experiments have provided insight into the preservation of magnetite in the sediments of the Maldives Inner Sea during early diagenesis. Here, we present high-resolution magnetic remanence data in the upper 15 meters of the sedimentary record, and detailed magnetic characterization on discrete samples from the upper 5.5 meters of the IODP Site U1471 record. It can be demonstrated that magnetite is rapidly reduced to greigite, with a large decrease in natural remanent magnetization below the upper two meters of the sedimentary record. The results suggest that current diagenesis could imprint almost 100,000 years of error in the chronology based on magnetostratigraphy. Element ratios data obtained from record U1471 also provided a detailed view of the changes of the Indian monsoon system on millennial timescales. Based on a refined chronology over the past 550,000 years, we reconstruct changes in the Indian Monsoon System on a scale of anomalies and verify their relationships with established records of the East Asian Monsoon System. The Fe/sum and Fe/Si records, shown that continental aridity in Asia tracks changes in sea level, while the intensity of winter monsoon winds responds to changes in Northern Hemisphere summer insolation. Furthermore, the anomalies in continental aridity and in the intensity of winter monsoon winds in millennial-scale events exhibit power in the precession band, almost in antiphase with Northern Hemisphere summer insolation. The good correspondence between our record and East Asian monsoon anomaly records suggests the occurrence of widespread anomalous arid events in Asia. In this same record, we further demonstrate, based on the high correlation of the Fe/K ratio with magnetic susceptibility, that during the middle to late Miocene, site U1471 received its load of detrital sediments mainly from the Ganges-Brahmaputra. Our data suggest that during the middle to late Miocene, the uplift of the Himalayas and the Tibetan Plateau strengthened the Indian Summer Monsoon and increased aridity in the Asian inland, initiating the deposition of red clay on the eastern Chinese loess plateau. In the NAP63 record, collected in São Paulo Bright, we demonstrate, based on the record of the high coercivity component of the acquisition of Isothermal Remanent Magnetization, that the delivery of sediments from the Rio da Prata was restricted due to the strong northeast winds during the intensification of the South America Summer Monsoon. We also demonstrate that during cold events in the Northern Hemisphere the South America Summer Monsoon was intensified.